Marine algae as attractive source to skin care. (3rd June 2017) - Berthon, Jean-Yves; Nachat-Kappes, Rachida; Bey, Mathieu; Cadoret, Jean-Paul; Renimel, Isabelle; Filaire, Edith
Abstract: As the largest organ in the human body, the skin has multiple functions of which one of the most important is the protection against various harmful stressors. The keratinised stratified epidermis and an underlying thick layer of collagen-rich dermal connective tissues are important components of the skin. The environmental stressors such as ultraviolet radiation (UVR) and pollution increase the levels of reactive oxygen species (ROS), contributing to clinical manifestations such as wrinkle formation and skin aging. Skin aging is related to the reduction of collagen production and decrease of several enzymatic activities including matrix metalloproteinases (MMPs), which degrade collagen structure in the dermis; and tissue inhibitor of metalloproteinases (TIMPs), which inhibit the action of MMPs. In addition to alterations of DNA, signal transduction pathways, immunology, UVR, and pollution activate cell surface receptors of keratinocytes and fibroblasts in the skin. This action leads to a breakdown of collagen in the extracellular matrix and a shutdown of new collagen synthesis. Therefore, an efficient antioxidants strategy is of major importance in dermis and epidermis layers. Marine resources have been recognised for their biologically active substances. Among these, marine algae are rich-sources of metabolites, which can be used to fight against oxidative stress and hence skin aging. These metabolites include, among others, mycosporine-like amino acids (MAAs), polysaccharides, sulphated polysaccharides, glucosyl glycerols, pigments, and polyphenols. This paper reviews the role of oxidative processes in skin damage and the action of the compounds from algae on the physiological processes to maintain skin health.